2018
DOI: 10.1111/apa.14222
|View full text |Cite
|
Sign up to set email alerts
|

Painful procedures can affect post‐natal growth and neurodevelopment in preterm infants

Abstract: Invasive painful procedures affected regular HC growth and short-term cognitive scores in preterm infants in the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…The number of painful procedures experienced in the first month of life is associated with lower cognitive development and head circumference at 1 year, although this is unlikely to be direct cause and effect [145]. Whilst the comfort of the baby needs to be considered, there is a tension between appropriate analgesia and the effects of sedation causing harm particularly when there is an emphasis of minimising duration of invasive respiratory support.…”
Section: Pain and Sedationmentioning
confidence: 99%
“…The number of painful procedures experienced in the first month of life is associated with lower cognitive development and head circumference at 1 year, although this is unlikely to be direct cause and effect [145]. Whilst the comfort of the baby needs to be considered, there is a tension between appropriate analgesia and the effects of sedation causing harm particularly when there is an emphasis of minimising duration of invasive respiratory support.…”
Section: Pain and Sedationmentioning
confidence: 99%
“…Pain management in preterm infants starting immediately after birth and in the first days of life is important, to avoid subsequent responses to painful procedures 26 and because repeated painful stimuli early in life lead to serious sequelae 5,12 . These include abnormal brain development, with lower cognitive scores and altered somatosensory and stress response systems 11,12 . The main finding of our study was that the LISA group required significantly more nonpharmacological pain relief in the first three days of life than the INSURE group, which might reflect an ongoing preterm stress response.…”
Section: Discussionmentioning
confidence: 65%
“…The less invasive surfactant administration (LISA) technique involves administering surfactant while maintaining spontaneous breathing using a thin catheter 10 . Endotracheal intubation in preterm infants is regarded painful and has a negative impact on brain development 11 . Illness severity in the first 24 hours of life together with pain exposure contributes to a slower microstructural brain development (corticospinal tract) up to term‐equivalent age 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Fortuitously, lag time problems may be useful in the identification of hypoglycemia in children with CHH where a spike in insulin and subsequent rapid drop in interstitial glucose may be earlier than a slower subsequent decrease in plasma glucose [11]. Current glucose monitoring requires frequent capillary sampling that exposes infants to procedural pain and stress that may contribute to altered neurodevelopment and affect short-term cog nitive scores in preterm infants [3,20]. It has been shown that the insertion of a CGMS device in preterm infants causes less pain than capillary blood sampling [21].…”
Section: All Glucose Measurementsmentioning
confidence: 99%